Beyond the slammed door - Anku, Solace Sefakor (Nordlit, 2015)
A Doll’s House (1879) is the most read of Ibsen’s plays in West Africa and the most performed. As the basis for the discourse on European emancipatory feminism, the play is presently being employed by selective dramatists in West Africa to contest the misinterpretation of the West African woman by European emancipatory feminists. Nora as a character creates a symbolic canvas on which the “real” African woman as envisaged by Tracie Utoh-Ezeajugh in her adaption titled Nneora: an African doll’s house (2005) is drawn. Owusu Janet, another dramatist, faces the issues from a conservative feminist point of view with her interpretation of the play influenced by her cultural perceptions of the woman.